Interleukin-4 and interleukin-13 inhibit the expression of leukemia inhibitory factor and interleukin-11 in fibroblasts - Souza, Pedro P. C. [UNESP]; Palmqvist, Py; Lundberg, Pernilla; Lundgren, Inger; Hanstrom, Lennart; Souza, Joao A. C.; Conaway, H. Herschel; Lerner, Ulf H. (Pergamon-Elsevier B.V. Ltd, 2012)
Cytokines produced by inflammatory or resident mesenchymal cells play important modulatory roles in the pathogenesis of inflammation induced bone loss. In the present study, the effects of IL-4 and IL-13 on the expression of three osteotropic cytokines in the IL-6 family expressed in human gingival fibroblasts were studied. IL-4R alpha and IL-13R alpha 1 mRNA were constitutively expressed in human gingival fibroblasts. The inflammatory cytokines IL-1 beta and TNF-alpha increased expression of IL-5, LIF, and IL-11 mRNA and protein in the gingival fibroblasts. Addition of IL-4 or IL-13 had no effect on IL-6 expression, but significantly inhibited LIF and IL-11 mRNA and protein stimulated by IL-1 beta and TNF-alpha. No involvement of NF-kappa B or STAT1 was observed in the inhibition. STAT6 was phosphorylated at Y641 by treatment with IL-4 and knockdown of STAT6 with siRNA decreased the inhibition of IL-11 and LIF expression by IL-4 in IL-1 beta and TNF-alpha stimulated cells. This study suggests that activation of STAT6 by IL-4 and IL-13, through type 2 IL-4 receptors, inhibits production of IL-11 and LIF stimulated by IL-1 beta and TNF-alpha in human gingival fibroblasts. A negative modulatory role of IL-4 and IL-13 in osteotropic cytokine production could be a mechanism playing an important inhibitory role in inflammation induced periodontitis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Interleukin-4; Interleukin-6; Gingival fibroblasts; Bone resorption